TINGKAT KEPUASAN MASYARAKAT NAGARI TARAM TERHADAP KEGIATAN P2MD DARI UKM P2I MENGENAI PEMANFAATAN TEKNOLOGI TEPAT GUNA DALAM MENGELOLAH LIMBAH ORGANIK - Kumbara; Ibnusina, Fedri; Shopia, Ikka Ade; Nofria, Rahma; Ilahi, Rendi Kurnia; Putri, Mai Viona; Elsa Angela, Elsa; Lubis, Naimatul Ardhiah (Green Engineering Society, 2023)
Service to the Nagari Taram community which has the potential to be developed in utilizing organic waste. If organic waste is not utilized and left alone, of course, it can have a negative impact on the majority of the community. So the solution offered in Village Community Empowerment (P2MD) activities is training in the application of appropriate technology in managing organic waste such as making eco enzymes from remaining organic waste, cultivating magot with feed from organic waste. The population of activities in Nagari Taram with a sample of participants were women and men, youth and others, this activity was carried out in July 2023. The method of this activity was carried out in the form of open meetings and direct training in the activity room, namely the Wali Nagari Taram office hall. Open meetings and training held in the activity room with the learning by doing method. Data collection through filling out questionnaires, observation, and direct observation Questionnaire filling was given to training participants to get the value of respondents from the Nagari Taram community from the training activities carried out. The result of this activity is that participants learn to understand the material and are accompanied by practice in the form of discussion forums where participants ask questions and consult about the handling of organic waste from the upstream to downstream sectors, raising awareness of the Nagari Taram community to be able to utilize organic waste into a valuable material.